2007
DOI: 10.1080/00365510601153353
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma glutathione peroxidase concentration in acute severe asthma: Comparison with plasma glutathione peroxidase activity, selenium and malondialdehyde

Abstract: Patients with acute severe asthma demonstrated increased MDA levels but no differences in plasma selenium levels or GPx activity. GPx levels measured by ELISA were elevated in severe asthma. These results are consistent with an adaptive up-regulation of GPx to protect against oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 44 publications
4
23
1
2
Order By: Relevance
“…However, in this study, neither Cu nor Co and Mn were associated with asthma prevalence. Several studies have been carried out to evaluate the association between minerals and asthma [6,7,[20][21][22]. In agreement with our nail-derived results, some of these studies show lower blood/plasma or serum levels of Se in asthmatics [8,23,24].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, in this study, neither Cu nor Co and Mn were associated with asthma prevalence. Several studies have been carried out to evaluate the association between minerals and asthma [6,7,[20][21][22]. In agreement with our nail-derived results, some of these studies show lower blood/plasma or serum levels of Se in asthmatics [8,23,24].…”
Section: Discussionsupporting
confidence: 90%
“…However, there is consistent contrary evidence [26]. Also, there are studies showing an association between high serum/plasma concentrations of Zn and Se in asthmatics as well as studies stating there are no associations between these variables [1,7,20,21]. Based on this conflicting evidence, it is difficult to say whether Se and Zn are involved in asthma pathogenesis and therefore have potential for the treatment and prevention of this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…For some of the analyses, the numbers of patients presenting with symptoms in each quartile were quite small, which might have masked any possible association. These observations concur with those of studies in adults that have shown no effect of selenium on atopy or asthma, but not with others that have shown an association .…”
Section: Discussionsupporting
confidence: 89%
“…At one level, GPx activities reflect selenium status as measured by plasma selenium, as indicated by the significant correlation between selenium concentrations and WBGPx activities in the present study. A number of investigators report lowered GPx activities along with lower selenium concentrations in children [18] and adults [15,19] with asthma, whereas Jacobson et al [16] found elevated concentrations of GPx (but not activities) in adults with severe asthma, suggesting that an adaptive up-regulation of GPx to protect against oxidative stress had occurred.…”
Section: Discussionmentioning
confidence: 99%
“…However, in case-control studies in India, Nadeem et al found significantly reduced activity in asthmatics compared to non-asthmatics, but slightly increased activity in asthmatics with acute exacerbations [12,30]. Other studies have revealed a significant negative association between asthma and GPX activity in platelets [31,32], but no association between asthma and GPX activity in plasma [33]. One of the differences between these case-control studies and the present study derived from the general population is that our cases were less well defined.…”
Section: Discussionmentioning
confidence: 98%